EFFECT OF HUMIC ACID AND MIXED HERBS ON PHYSIOLOGICAL, HEMATOLOGICAL AND BIOCHEMICAL VALUES ON GOATS IN INDONESIA - Dwatmadji,; T. Suteky,; E. Soetrisno, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to determine the effect of mixed herbs and humic acid supplementation on the physiological status, haematological, and biochemical values of local goats in Indonesia. Twenty-four local goats 7-8 months old, were divided into four groups of six goats each. T0: herbs without humic acid, T1: herbs with 2-gram humic acid/goat T2: herbs and 4-gram humic acid/goat; T3: herbs and 6-gram humic acid/goat. The goats were fed grass and fermented oil palm. The result found that Orthogonal contrasts detect (P< 0.001) a significant influence of humic acid addition on respiration and heart rate, as well as HTC, with the amount of addition varying considerably during the 12.00 observation. There are no alterations in erythrocyte indices, leucocytes increase quantitatively with neutrophils rising significantly in line with the presence of humic acid. Humic acid lowers serum cholesterol while boosting protein levels in the blood. In summary, humic acid impacts physiological and haemato-biochemical parameter of local goats in Indonesia.